2013
DOI: 10.1186/1471-230x-13-30
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ABCG8 19H risk allele in cholesterol absorption and gallstone disease

Abstract: BackgroundGallstone disease is associated with p.D19H of ABCG8 as well as alterations of cholesterol and bile acid metabolism. However, molecular mechanisms have not been fully elucidated. It is important to understand the link between the sterol transporters ABCG5/8 and NPC1L1 and intestinal cholesterol absorption as well as de novo synthesis in gallstone patients stratified according to 19H risk allele. Moreover, the functional importance of the 19H variant on intestinal ABCG8 feature remains to be clarified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 61 publications
(84 reference statements)
1
22
0
Order By: Relevance
“…Our findings that low plant sterol levels in individuals with GD were observed both before and after obesity surgery, in those with and without previous LCC, and independent of NAFLD,supporttheconclusionthatcholesterolandplantste-rolmetabolismareprimarilyalteredinGD.Theseresultsarein line with the results from Krawczyk et al [11] who also found that serum sterols were lower in patients with GD compared to those without GD. These results also support the idea that low levelsofserumplantsterolsarerelatedtoGDitself,potentially partlyduetogeneticregulationbyABCG5/8genes [17,19,20,31].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings that low plant sterol levels in individuals with GD were observed both before and after obesity surgery, in those with and without previous LCC, and independent of NAFLD,supporttheconclusionthatcholesterolandplantste-rolmetabolismareprimarilyalteredinGD.Theseresultsarein line with the results from Krawczyk et al [11] who also found that serum sterols were lower in patients with GD compared to those without GD. These results also support the idea that low levelsofserumplantsterolsarerelatedtoGDitself,potentially partlyduetogeneticregulationbyABCG5/8genes [17,19,20,31].…”
Section: Discussionsupporting
confidence: 82%
“…As plant sterols are not synthesized in the human body, their serum levels have been used to estimate the function of hepatic and intestinalcholesterol transporters [14]. Interestingly, variants in the ABCG5/8 transporters that associate with changes in sterol transport alsocontribute to cholesterol gallstone formation suggesting a common etiology [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The quality and quantity controls of isolated material were assessed as reported. 22 Blood samples (3-5 ml) were used for determination of total serum cholesterol and triglyceride levels as well as for bile acid metabolism profiling (measurements of bile acid synthesis markers, serum bile acid, and FGF19 concentrations). Serum triglycerides and cholesterol levels were analysed by standard clinical tests.…”
Section: Subjects and Materialsmentioning
confidence: 99%
“…In fact, mutations and polymorphisms in ABCG5 and ABCG8 genes were identified in these patients (7). In other studies, the involvement of ABCG8 gene polymorphisms D19H and Y54C/T400K have been associated with the development of gallstone disease in German, Romanian, Scandinavian, Chinese and Indian populations, among others (8,9). Recently, a genome-wide association study meta-analysis conducted by Joshi et al (10) revealed the association of two ABCG8 gene polymorphisms, rs11887534 and rs4245791, with the risk of developing gallstones.…”
Section: Introductionmentioning
confidence: 74%